A case study on corporate social responsibility on tax exemption - Nor Suraini, Mohd Hassan; Diyana, Kamarudin; Tengku Awalul Hawa, Yahaya (Future Academy, 2019)
This preliminary research is a study on the corporate social responsibility of Malaysian corporate company’s selection in channelling their fund to a needy person or organization. Evaluation has been done to a Malaysian east coast regent company. Nowadays, company’s awareness level on corporate social responsibility (CSR) is high. As such, the effort in nourishing the awareness will be worthless should the company channels it to the wrong party. Furthermore, the said company might be refused for tax exemption entitlement. Therefore, there are specific criteria to be fulfilled in selecting the ideal personnel or organization. Besides, it is essential for the company to have a crystal-clear view on CSR type that have been designated for them; to qualify them for tax exemption. As such, qualitative method is used in determining which factors of a person or an organization criterion is/are most contributed to channel funds. Researcher will analyse gathered data from participants and compared it to the existing method used in Malaysia. The outcome might be useful corporate companies; as which it can be used as guidelines in measuring their current performance of collecting tax; resulting in correct allocation of fund and contribution to the righteous parties.